A psychosociospiritual collaborative governance model with marriage guidance to prevent child marriage in Indonesia - Fadhilah, Ningsih; Kustini, Kustini; Atieqoh, Siti; Pranawati, Rita; Rahmatullah, Andi Muhammad Ridha (UIN Ar-Raniry Banda Aceh, 2025)
The high prevalence of child marriage in Indonesia has become a pressing issue, not only at the national but also at the global level. Preventive efforts require a collaborative and multi-faceted approach that goes beyond legal regulations and incorporates social, psychological, spiritual dimensions, as well as marriage guidance. This article aims to explore a collaborative psychosocial-spiritual governance model that integrates marriage guidance in the prevention of child marriage in Indonesia. This research was conducted using an exploratory qualitative approach in Jombok Village, Trenggalek, East Java, and Woro Village, Rembang, Central Java. Data was collected through in-depth interviews with various stakeholders including government officials, religious leaders, local psychologists and cultural figures, local activists, NGOs, as well as couples/families experiencing child marriage. The research results indicate that social innovation for preventing child marriage is implemented through the principles of collaborative governance based on a psychosocial-spiritual approach, with multi-level involvement from villages, sub-districts, to districts. Education, mentoring, and marriage counseling programs are carried out in stages, encompassing social assistance based on child protection, psychological support, and strengthening religious values. This approach demonstrates that effective prevention strategies are not only focused on formal regulations but also on value transformation, community capacity building, and creating an ecosystem that supports children's rights. The overall efforts aim at preventing child marriage in a more holistic, inclusive, gender-just manner, and contextualized with the local values of Indonesian society.